2011
DOI: 10.1007/s10964-011-9633-y
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Gender, Depression, and Cigarette Smoking Among U.S. Hispanic Youth: The Mediating Role of Perceived Discrimination

Abstract: Hispanic youth are at risk for experiencing depressive symptoms and smoking cigarettes, and risk for depressive symptoms and cigarette use increase as Hispanic youth acculturate to U.S. culture. The mechanism by which acculturation leads to symptoms of depression and cigarette smoking is not well understood. The present study examined whether perceived discrimination explained the associations of acculturation with depressive symptoms and cigarette smoking among 1,124 Hispanic youth (54% female). Youth in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 44 publications
6
101
0
Order By: Relevance
“…However, discrimination research among adolescents most consistently has found associations with internalizing problems. Among Latino adolescents, perceived discrimination is associated cross-sectionally with more depressive symptoms (Behnke et al 2011;Huynh and Fuligni 2010;Lorenzo-Blanco et al 2011) and somatic symptoms (Huynh and Fuligni 2010). There is also evidence of longitudinal associations between discrimination and more depressive symptoms and lower self-esteem among both Asian and Latino high school adolescents (Greene et al 2006) and more anxiety and depression among Latino middle school adolescents (Berkel et al 2010).…”
Section: Implications Of Microaggressionsmentioning
confidence: 96%
“…However, discrimination research among adolescents most consistently has found associations with internalizing problems. Among Latino adolescents, perceived discrimination is associated cross-sectionally with more depressive symptoms (Behnke et al 2011;Huynh and Fuligni 2010;Lorenzo-Blanco et al 2011) and somatic symptoms (Huynh and Fuligni 2010). There is also evidence of longitudinal associations between discrimination and more depressive symptoms and lower self-esteem among both Asian and Latino high school adolescents (Greene et al 2006) and more anxiety and depression among Latino middle school adolescents (Berkel et al 2010).…”
Section: Implications Of Microaggressionsmentioning
confidence: 96%
“…Thus, how gender impacts the likelihood of experiencing a cultural value gap has not been fully elucidated. Moreover, Latina girls are more likely to report depressive symptoms than boys (Lorenzo-Blanco et al 2011). Therefore, their greater risk may be in part associated with greater cultural gaps or greater impact associated with the gap.…”
Section: Gendermentioning
confidence: 99%
“…Hispanic youth experience discrimination, and boys report more discriminatory experiences than girls (Lorenzo-Blanco et al, 2011). Moreover, acculturation has been linked with more frequent discrimination in boys and girls (Kam, Cleveland, & Hecht, 2010), and discrimination links with elevated smoking in Hispanic boys (Wiehe, Aalsma, Liu, & Fortenberry, 2010) and girls (Lorenzo-Blanco et al, 2011).…”
Section: Everyday Discrimination and Family Functioningmentioning
confidence: 99%